2020
DOI: 10.1016/j.jinf.2020.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of COVID-19 infection in Beijing

Abstract: s u m m a r yBackground: Since the first case of a novel coronavirus infection pneumonia was detected in Wuhan, China, a series of confirmed cases of the COVID-19 were found in Beijing. We analyzed the data of 262 confirmed cases to determine the clinical and epidemiological characteristics of COVID-19 in Beijing. Methods: We collected patients who were transferred by Beijing Emergency Medical Service to the designated hospitals. The information on demographic, epidemiological, clinical, laboratory test for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

62
788
19
41

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,080 publications
(946 citation statements)
references
References 11 publications
62
788
19
41
Order By: Relevance
“…These asymptomatic patients could cause familial clusters [15]. According to Tian et al, asymptomatic infection rate was 5%, whereas in Diamond Princess Cruise Ship berthed at Tokyo Bay, Japan, it was nearly 18% [16,17]. Among a total of 72,314 China's cases, 889 were classified as asymptomatic (1%) [9].…”
Section: Asymptomatic Infectionmentioning
confidence: 99%
“…These asymptomatic patients could cause familial clusters [15]. According to Tian et al, asymptomatic infection rate was 5%, whereas in Diamond Princess Cruise Ship berthed at Tokyo Bay, Japan, it was nearly 18% [16,17]. Among a total of 72,314 China's cases, 889 were classified as asymptomatic (1%) [9].…”
Section: Asymptomatic Infectionmentioning
confidence: 99%
“…According to a Chinese study, among of 262 patients, 46 (17.6%) were severe cases, 216 (82.4%) were common cases, which including 192 (73.3%) mild cases, 11 (4.2%) non-pneumonia cases and 13 (5.0%) asymptomatic cases, respectively. [20] Also, Mizumoto et al [21] showed that the estimated asymptomatic proportion was 17.9% (95% credible interval (CrI): 15.5-20.2%) within the population onboard a cruise ship called the Diamond Princess. However, in an open letter to the authorities in the Tuscany region, Romagnani wrote that the vast majority of people infected with COVID-19, 50-75% were asymptomatic, but represented "a formidable source" of contagion.…”
Section: A Face Mask Must Be Placed On the Patient Even If The Patiementioning
confidence: 99%
“…Finally, the familial cluster infected with COVID-19 has been reported in homes or hospital, especially without obvious symptoms [4]. According to our recent study, 5% of COVID-19 infection were asymptomatic cases [5]. If the asymptomatic cases cannot be found or isolated appropriately for medical observation, they will spread the virus to other close contacts quickly.…”
mentioning
confidence: 96%